An Analysis of Current Decrease in Generators at the Hydrogen Plant PLTU Pangkalan Susu - Rizky Purba; Adi Sastra P. Tarigan; Hamdani (CERED Indonesia Institute, 2022)
The hydrogen generator is one of the devices used to cool the main generator. The hydrogen produced by the hydrogen generator is sent to the main generator to reduce the very high temperature. The hydrogen generator system is the hydrogen obtained from the electrolyte. After the electrolysis process, it flows into the generator to cool the main generator. The PLTU Pangkalan Susu hydrogen power plant was interrupted by a sudden power drop. As a result, the system tripped, cutting off the supply of hydrogen injected to the generator. According to the analysis, the reason for the current drop is that the electrolyte concentration value is low. in order to replace it in such a way that the current in the generator returns to normal.